ANALISIS PERSEPSI PEMUSTAKA TERHADAP KUALITAS LAYANAN PERPUSTAKAAN IAI SAHID BOGOR BERDASARKAN LIMA DIMENSI PELAYANAN TJIPTONO - Ima Rahmawati; Reva Luthfiah Asshidqi; Muzhir Ihsan (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2026)
The purpose of this study is to investigate how consumers perceive the quality of services offered by the Library of IAI Sahid Bogor by applying Tjiptono's five characteristics of service quality: tangibles, assurance, responsiveness, empathy, and reliability. Data was gathered using a qualitative descriptive approach, which included direct observation of library service activities and in-depth interviews. Diverse user experiences and viewpoints are revealed by the findings, which emphasize that while responsiveness and the availability of supporting facilities still need to be improved, reliability and empathy are generally valued. These observations offer important information for improving service plans going forward and give a deeper understanding of how patrons see the quality of library services.